Karl Mannheim and the liberal telos of realism. (September 2019) - Hvidsten, Andreas H
The renaissance of classical realism in International Relations (IR) has highlighted the close historical and conceptual connection between realism and liberalism. In this essay, I consider an underexplored epistemological dimension of this connection using Karl Mannheim's Ideology and Utopia – an influential work for classical IR realists and an important treatise on political theory in its own right. Based on Mannheim's argument, I make the case that (a certain kind of) liberalism is the telos of (a certain kind of) realism: that the natural endpoint of the inherent logic of realism is a form of liberalism. I argue that completing the epistemological and political critique that leads to realism by also putting the realist position itself under (self-)examination, unearths a liberal outlook as its foundation. Explicating this dialectic adds a new dimension to the many other points of contact between realism and liberalism that have been explored by IR scholars in recent years, and it provides a new link between this scholarship and the literature on the epistemological foundations of classical realism. Finally, the essay is an argument for a closer engagement with Mannheim in an IR context, both as a philosopher of knowledge and as a political thinker.